The effect of pelvic floor muscle fatigue on stress urinary incontinence: A systematic review - Misa Naghdipour; Farnoosh Ebrahimzadeh; Malihe Azadehrah; Aynaz Boostan (Mashhad University of Medical Sciences, 2021)
Introduction: Due to the lack of systematic studies which can add new information on the relationship between pelvic floor muscle fatigue and stress urinary incontinence, this systematic study was performed with aim to investigate the effect of pelvic floor muscle fatigue on stress urinary incontinence. The results of this study will be useful for planning strategies for the prevention and treatment of evidence-based stress urinary incontinence. Methods: In this systematic review study which was performed based on the PRIZMA statement, the observational and clinical trial studies published in PubMed, Scopus, EMBASE, PEDro, LILACS, SciELO, Cochrane Library, Google Scholar databases. CINAHL, SID and Iran Doc published until 2020 were evaluated. Good quality articles (scoring≥ 70) based on the Downs and Black scale were included in this study. Results: In the initial search, 2301 articles were found and in the later stages, 2296 articles were deleted and 5 articles were included in this systematic review. The results of one study did not show an association between muscle fatigue and stress urinary incontinence, and three articles showed a strong association between muscle fatigue and stress urinary incontinence. One article also showed that pelvic floor muscle fatigue cannot cause stress urinary incontinence. Conclusion: Pelvic floor muscle fatigue can affect the progression or worsening of stress urinary incontinence; however, due to the lack of number of studies and the heterogeneity of studies in this field, conclusions should be used with caution.